Treatment cessation in noncirrhotic, e‐antigen negative chronic hepatitis B is safe and effective following prolonged anti‐viral suppression with nucleosides/nucleotides. Issue 7 (11th August 2014) - Patwardhan, V. R.; Sengupta, N.; Bonder, A.; Lau, D.; Afdhal, N. H.
Summary Background The treatment of HBeAg‐negative chronic hepatitis B (CHB) is considered to be open‐ended, with no guidelines for treatment cessation. Aim To evaluate biochemical and virological relapse requiring retreatment in noncirrhotic HBeAg‐negative CHB in patients who stopped treatment following a period of prolonged viral suppression with nucleotides/nucleosides. Methods We performed a single‐centre retrospective chart review of patients with HBeAg‐negative CHB who maintained viral suppression for 4–5 years on anti‐viral treatment, and thus subsequently stopped treatment. The primary end point of composite relapse was defined by an increase in HBV DNA >2000 IU/mL, ALT elevation above 1.25 ×  normal or doubling of ALT from cessation, and re‐initiation of anti‐viral therapy. Results We identified 33 patients with HBeAg‐negative CHB who stopped treatment following viral suppression. Mean treatment duration was 5.28 ± 2.73 years. Patients were treated with lamivudine (3), adefovir (14), entecavir (4), and tenofovir (12). Eleven (33%) patients met the primary end point of composite relapse. For individual end points, 21 (63%) patients had a viral relapse, 16 (48%) had a biochemical relapse, and 16 (48%) restarted treatment, leaving 17 (52%) patients who remained treatment‐free over a median 36 months of follow‐up. Lower pre‐treatment ALT and detectable HBV DNA within the first month after treatment discontinuation were associated with increased rates of composite relapse (HR 1.01; P = 0.022 for ALT and HR 1.01; P = 0.038 for HBV DNA). Conclusion Patients with noncirrhotic HBeAg‐negative CHB can stop treatment after greater than 4–5 years of suppressive therapy with nucleosides/nucleotides with more than 50% remaining treatment‐free.